Store support for local producers as a driver of legitimacy and purchase intentions: A moderated mediation model. (25th March 2023) - Odou, Philippe; Schill, Marie; Chaney, Damien; Roznowicz, Corentin
Abstract: As part of their corporate social responsibility strategies, large retailers have recently been offering an increasing number of local products. However, the impact of such actions is not obvious, since large retail stores are expected to offer industrial products in large quantities at low prices, yet local products are manufactured in small quantities with high quality at a higher cost. Drawing on institutional theory, this research therefore investigates the impact of these actions on the perceived legitimacy of a retailer. To test the hypotheses, two scenario-based experiments were conducted. Study 1 (n = 125) indicates that the perceived legitimacy of the retail store mediates the effect of support for local producers on patronage intentions. This mediating effect of legitimacy is moderated by locavorism and thus occurs only when consumers prefer local products. Study 2 (n = 171) replicates the results of Study 1 and shows that stores communicating that their support came 'without earning a cent' have a greater impact on patronage intentions than those that communicated local support but 'with a classic margin'. This study thus contributes to the literature that investigates the role of retailers in promoting sustainability.